Glycyrrhetinic acid regulates impaired macrophage autophagic flux in the treatment of non-alcoholic fatty liver disease - Fan, Yadong; Dong, Wenjin; Wang, Ying; Zhu, Shan; Chai, Rundong; Xu, Zhe; Zhang, Xiaoyu; Yan, Yiqi; Yang, Long; Bian, Yuhong (Frontiers in Immunology, 2022)
Macrophages are involved in hepatocyte steatosis and necroinflammation, and play an important role in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Impaired autophagy function (decreased autophagy or blocked autophagic flow) leads to cell damage and death and promotes NAFLD progression. The experimental and clinical research of Glycyrrhetinic acid (GA) in the treatment of NAFLD has gradually attracted attention with clear pharmacological activities such as immune regulation, antiviral, antitumor, antioxidant, liver protection and anti-inflammatory. However, the effects of GA on the STAT3-HIF-1α pathway and autophagy in macrophages are still unclear, and its mechanism of action in the treatment of NAFLD remains to be further elucidated. We constructed NAFLD mouse model through a high-fat and high-sugar diet to investigate the therapeutic effects of GA. The results showed GA reduced weight, improved the pathological changes and hepatic lipid deposition of liver and abnormally elevated levels of serum biochemical (AST, ALT, TG, T-CHO, LDL-C and HDL-C) and inflammatory indexes (IL-1β, IL-4, IL-6, MCP-1 and TNF-α) in NAFLD mice. Further examination revealed GA ameliorates excessive hepatic macrophage infiltration and hepatocyte apoptosis. The results of the cell experiments further elaborated GA modulated PA-induced macrophage STAT3-HIF-1α pathway and ameliorated impaired autophagic flux (blockade of autophagosome-lysosome fusion) and overactivation of inflammation. Excessive hepatocyte apoptosis caused by the uncontrolled release of inflammatory cytokines was also suppressed by GA. Conclusion: This study demonstrated that GA could regulate the STAT3-HIF-1α pathway of macrophages, ameliorate the impaired autophagy flux and reduce excessive production of inflammatory cytokines to improve the excessive apoptosis of liver cells, thus playing a therapeutic role on NAFLD.